Use of a motus sleeve during the care of a medial elbow injury in the high school baseball athlete: Level 3 case report - Brodersen, J. M.; Carlson, M. H.; Govrik G. L.; Chmielewski, T. L. (Journal of Athletic Training, 2019)
"Background: Incidence of medial elbow injuries among youth pitchers is increasing. Throwing mechanics including lower arm slot, faster arm speed, and higher maximal shoulder external rotation are associated with greater elbow varus torque and may contribute to medial elbow injury. Wearable technology allows objective measurement of throwing mechanics. No studies have reported on this technology in the injured high school athlete. Patients or Other Participants: The athlete is an 18 year old right-handed baseball pitcher. He presented to the Athletic Trainer after 3 weeks of competition and 4-days post pitching with medial elbow pain. Evaluation revealed tenderness at the medial epicondyle and fl exor pronator mass, full active elbow ROM, 4+/5 forearm fl exor strength, and no visible edema. Valgus stress test was negative while valgus extension overload and moving valgus stress tests were positive for pain. Referral to a physician confi rmed a fl exor- pronator mass strain by physical exam. Physical therapy followed including 2 visits consisting of dry needling to forearm fl exors, and shoulder and elbow strengthening. Treatment was also provided in the athletic training room consisting of performing the strengthening program and instrument assisted soft tissue mobilization. The medical team and athlete agreed that he would discontinue pitching but would continue playing in the fi eld. Following 1 week of rest from throwing the athlete began infield play with some discomfort. He returned to pitching in a limited capacity after 3 weeks of treatment. Intervention(s): Prior to the season, the athlete completed a Kerlan-Jobe Orthopaedic Clinic Shoulder and Elbow questionnaire (KJOC) and was issued a motusBaseball system, a validated inertial measurement unit containing a triaxial accelerometer and gyroscope, held within a compression sleeve. He was instructed in proper sensor positioning on the arm (5cm distal to the medial epicondyle of the humerus). The sensor was to be worn during warm-up, long toss, bullpen, and live game activity. Variables collected for each throw included arm slot, maximal shoulder external rotation, arm speed, and elbow varus torque. Data was stored in the sensor until upload to an application via Bluetooth. The athlete was asked to upload data weekly. The sensor was worn for 9 weeks, from the fi rst week of competition to the end of the season. KJOC and informed consent were completed post-season. In addition to traditional management of medial elbow injury, throwing metrics were quantifi ed by the athletic trainer, providing additional insight to injury development. Outcomes or Other Comparisons: High effort throws (52 to 67 N-m) were retrospectively analyzed. Sensor variables were averaged weekly, except during the week of rest (Table 1). The athlete showed variability in arm slot, the largest difference being a 22.8 degree decrease from week 1 to 2, one week before injury. Maximal shoulder external rotation increased 13.5 degrees over the 9 week period. Elbow varus torque was highest upon return to pitching (Week 7). Subsequently both arm speed and elbow varus torque decreased in the fi nal 2 weeks of the season. KJOC score decreased from 69 at preseason, to 60 at post season. Conclusions: Variability in throwing mechanics was evident, with demonstrated risk factors for medial elbow injury both acutely (arm slot), and cumulatively (shoulder external rotation). Poorer throwing mechanics at the end of the season agrees with decrease in KJOC score from pre-to post-season. Workload (throw counts) may not be accurate due to noncompliance with recording and upload, preventing analysis of workload during injury development and return to throwing. Clinical Bottom Line: Quantifi ed throwing metrics during the season provided insight into medial elbow injury development and return to throwing. Use of a Motus sleeve may augment preventative and post injury care provided to the high school athlete."